Understanding Cultural Differences Towards English-Speaking Countries in English Camp Program 2019 - Iin Rachmawati (Penerbit STKIP PGRI Bangkalan, 2019)
The term cultural differences had long been known by a lot of people all around the world, but only a few of them knows about cultural differences happened in English training program by English Education Department just like English Camp Program. Due to that reason, the researcher is interested in digging more about the cultural differences towards English-speaking countries in English Camp Program 2019 in relation to the understanding of college students about some foreign cultures. In general, this research will use qualitative descriptive method because the main goal is to describe about students’ understanding on cultural differences through that English Camp Program. More specifically, this research will use receptive approach along with sinchronic method because it is only observe about the phenomena which happened in certain period of time. The result shows that students can understand about cultural differences in English-speaking countries through debating, public speaking, and presenting what’s on their booth. Cultures understood during the program are about tourist attractions, culinary aspects, myths and legends, people’s habits and ideas, music and dance, government system, arts and festivals, region and religion. Moreover, the students will enable to understand cultures quickly and easily if they are given the information practically rather than theoretically like giving materials in the classroom.